Prolyl isomerase Pin1 negatively regulates the stability of SUV39H1 to promote tumorigenesis in breast cancer. Issue 11 (9th August 2013) - Khanal, Prem; Kim, Garam; Lim, Sung‐Chul; Yun, Hyo‐Jeong; Lee, Kwang Youl; Choi, Hoo‐Kyun; Choi, Hong Seok
Abstract : Pin1, a conserved eukaryotic peptidyl‐prolyl cis/trans isomerase, has profound effects on numerous key‐signaling molecules, and its deregulation contributes to disease, particularly cancer. Although Pin1‐mediated prolyl isomerization of protein servers as a regulatory switch in signaling pathways, the significance of proline isomerase activity in chromatin modifying complex remains unclear. Here, we identify Pin1 as a key negative regulator for suppressor of variegation 3–9 homologue 1 (SUV39H1) stability, a major methyltransferase responsible for histone H3 trimethylation on Lys9 (H3K9me3). Pin1 interacts with SUV39H1 in a phosphorylation‐dependent manner and promotes ubiquitination‐mediated degradation of SUV39H1. Consequently, Pin1 reduces SUV39H1 abundance and suppresses SUV39H1 ability to induce H3K9me3. In contrast, depletion of Pin1 in cancer cells leads to elevated SUV39H1 expression, which subsequently increases H3K9me3, inhibiting tumorigenecity of cancer cells. In a xenograft model with 4T1 metastatic mouse breast carcinoma cells, Pin1 overexpression increases tumor growth, whereas SUV39H1 overexpression abrogates it. In human breast cancer patients, immunohistochemical staining shows that Pin1 levels are negatively correlated with SUV39H1 as well as H3K9me3 levels. Thus, Pin1‐mediated reduction of SUV39H1 stability contributes to convey oncogenic signals for aggressiveness of human breast cancer, suggesting that Pin1 may be a promising drug target for anticancer therapy.—Khanal, P., Kim, G., Lim, S.‐C, Yun, H.‐J., Lee, K. Y., Choi, H.‐K., Choi, H. S. Prolyl isomerase Pin1 negatively regulates the stability of SUV39H1 to promote tumorigenesis in breast cancer. FASEB J . 27, 4606–4618 (2013). www.fasebj.org